2015
DOI: 10.1007/s00249-015-1087-9
|View full text |Cite
|
Sign up to set email alerts
|

Origin of pronounced differences in 77 K fluorescence of the green alga Chlamydomonas reinhardtii in state 1 and 2

Abstract: In response to changes in the reduction state of the plastoquinone pool in its thylakoid membrane, the green alga Chlamydomonas reinhardtti is performing state transitions: remodelling of its thylakoid membrane leads to a redistribution of excitations over photosystems I and II (PSI and PSII). These transitions are accompanied by marked changes in the 77 K fluorescence spectrum, which form the accepted signature of state transitions. The changes are generally thought to reflect a redistribution of light-harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Such a situation took place during dark‐adaptation and dark‐relaxation periods, as the gas diffusion inside the algal suspension in the microplate wells most probably was limited. A method used to provide the state 1 occurrence in dark‐adapted C. reinhardtii cells is strong agitation, which enables oxygen to penetrate into the culture (Ünlü et al ) but it is impossible to be applied for samples kept in multi‐well plate. On the other hand, portioning the well‐aerated, dark‐adapted cultures into the microplate in the darkness directly before the measurements is uncomfortable.…”
Section: Resultsmentioning
confidence: 99%
“…Such a situation took place during dark‐adaptation and dark‐relaxation periods, as the gas diffusion inside the algal suspension in the microplate wells most probably was limited. A method used to provide the state 1 occurrence in dark‐adapted C. reinhardtii cells is strong agitation, which enables oxygen to penetrate into the culture (Ünlü et al ) but it is impossible to be applied for samples kept in multi‐well plate. On the other hand, portioning the well‐aerated, dark‐adapted cultures into the microplate in the darkness directly before the measurements is uncomfortable.…”
Section: Resultsmentioning
confidence: 99%
“…State transitions were suggested to alter the thylakoid ultrastructure and protein-protein interactions in C. reinhardtii 16 . The process may also lead to switch of the detached LHCIIs into the energetically quenched form so as to avoid photodamage [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…A primary example of a mechanism that regulates this distribution in higher plants, algae and cyanobacteria are state transitions (ST) (van Thor et al 1998 ; Allen 2003 ; Bellafiore et al 2005 ; Drop et al 2014 ), for the first time observed in 1969 in 77 K fluorescence spectra of Porphyridium cruentum (Murata 1969 ). Many subsequent studies on ST have routinely included low-temperature fluorescence spectroscopy (Allen et al 1981 ; Wollman and Delepelaire 1984 ; Bruce et al 1985 ; Delphin et al 1995 ; Cardol et al 2003 ; Bellafiore et al 2005 ; Kargul et al 2005 ; Chuartzman et al 2008 ; Iwai et al 2008 ; Allorent et al 2013 ; Drop et al 2014 ; Ünlü et al 2016 ). It is commonly accepted that redistribution of excitation energy between PSI and PSII upon state transitions is realized by a shift of a part of the light-harvesting antenna of PSII (LHCII) between PSII (state 1; St1) and PSI (state 2; St2).…”
Section: Introductionmentioning
confidence: 99%